Towards improving Subolesin and MSP-based vaccines targeting Rhipicephalus microplus and Anaplasma phagocytophilum - Maritz-Olivier, Christine (University of Pretoria, 2024)
Dissertation (MSc (Genetics))--University of Pretoria, 2024.